Ethics and university teaching. Perceptions and new challenges - Zeledón Ruiz, María del Pilar (2020)
This article presents the perception that the professors of the School of Business Administration (EAN) of the University of Costa Rica have about ethics and university teaching. For this, through a mixed design of a dominant qualitative approach, based on a sociocritical paradigm, dynamic inquiries and scientific results were supported more solidly, to generate self-reflection and promote educational transformation. In this sense, a self-administered survey was applied to 147 academics, complemented with phone calls and face-to-face interviews. The results highlight the high degree of importance that teachers provide to ethics in vocational training, as well as the strategies and values that should characterize the professional in Business. The conclusions reaffirm the need to strengthen ethical performance in the professional performance of students. It is also highlighted that these professionals with ethical principles develop soft skills (teamwork, communication, leadership) and establish better human and organizational relationships.